2020
DOI: 10.4103/jfmpc.jfmpc_700_20
|View full text |Cite
|
Sign up to set email alerts
|

A study on diabetic foot ulcers in Central rural India to formulate empiric antimicrobial therapy

Abstract: Aim: This study was carried out on patients with diabetic foot ulcer (DFU) to assess the clinical characteristics, spectrum of microbial flora, antibiotic sensitivity, and devise an empiric antimicrobial therapy. Material Methods: Clinical data and tissue samples were collected from 105 diabetic foot ulcer patients between December 2018 and November 2019. The collected samples were processed as per Clinical and Laboratory Standards Institute guidelines and clinical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
(21 reference statements)
2
5
0
Order By: Relevance
“…This epidemiology was similar to Singh A et al, which showed most of the patients between the age of 45-64, with a male to female ratio of 2.28:1 [5]. In the study by Yerat al., male preponderance was seen with approximately a 1.5:1 ratio, showing almost 60.5% male subjects and 39.5% females with a mean age around 54.9 years [6].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This epidemiology was similar to Singh A et al, which showed most of the patients between the age of 45-64, with a male to female ratio of 2.28:1 [5]. In the study by Yerat al., male preponderance was seen with approximately a 1.5:1 ratio, showing almost 60.5% male subjects and 39.5% females with a mean age around 54.9 years [6].…”
Section: Discussionsupporting
confidence: 87%
“…Most patients of advanced grade (3)(4)(5) showed poorly managed diabetes, with peripheral neuropathy and peripheral vasculopathy being significant predictors of diabetic foot. In our study, diabetic neuropathy and vasculopathy were seen more in patients with increased HbA1c, advancing age, increased random blood sugar, and increased duration of diabetes mellitus and showed increased amputation risk in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding of mono-microbial infections versus polymicrobial infections, the current study showed that 56.72% of DFU patients had poly-microbial infections (the isolation of two or more bacteria), In contrast studies [24,31] revealed that 83% and 75% of patients, respectively, had poly-microbial infections. In contrast, a study by [32], which showed that 48.57% of samples revealed a single organism, a study by [32], which found that 28.57% of samples revealed two organisms, and a study by [33] which discovered that 62.2% of wound cultures had monomicrobial growth and 27.1% had polymicrobial development. These outcomes may be explained based on the length of DFIs, the severity of the ulcer, and empirical antimicrobial medicines.…”
Section: Discussionmentioning
confidence: 95%
“…There were 30 studies conducted in Asian countries that discussed the microbiology of wound infections and the prevalence of P. aeruginosa ( Figure 1 ). Countries that were represented in the literature search included China [ 69 , 70 , 71 ], India [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ], Indonesia [ 83 , 84 ], Iran [ 85 , 86 ], Kuwait [ 87 ], Lebanon [ 88 ], Malaysia [ 89 , 90 , 91 ], Pakistan [ 92 , 93 , 94 ], Singapore [ 95 ], Turkey [ 96 ], and Iraq [ 97 ]. Most of the included studies focused on diabetic foot infections, and the frequency of P. aeruginosa isolation was therefore comparable when all chronic wound infections were evaluated or if diabetic foot infections specifically were analyzed ( Figure 1 and Figure 2 ).…”
Section: Prevalence Of P Aeruginosa In Wound Infec...mentioning
confidence: 99%
“…Contrary to the rest of the continent, P. aeruginosa was the most abundant pathogen in India and Malaysia. Of the 11 studies that took place in India, five of the investigations found that P. aeruginosa was the most commonly isolated organism, which was followed by S. aureus and members of the order Enterobacterales (mainly Escherichia coli and Klebsiella pneumoniae ), respectively [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. The reported frequency of P. aeruginosa isolation was also relatively consistent with a range of 16–30% in every Indian study.…”
Section: Prevalence Of P Aeruginosa In Wound Infec...mentioning
confidence: 99%